Canine mammary gland tumours diagnosed at Veterinary Histopathology Laboratory, Faculty of Veterinary Medicine, Universiti Putra Malaysia 2006–2012 - Sahabi, Kabiru; Selvarajah, Gayathri Thevi; Saad, Zamri; Mustaffa, Mohd Noordin; Kumar Sharma, Reuben Sunil; Mohd Yusof, Mohd Sabri; Omar, Mohd Ariff; Dhaliwal, Gurmeet Kaur; Sabri, Jasni (UPM-MAKNA Cancer Research Laboratory, Institute of Bioscience, 2014)
Dogs develop neoplasia naturally and spontaneously just like in humans. Mammary gland tumour is the most common neoplasm in female dogs. Age of dog, neuter status, breed size and pedigree have all been described to significantly affect the risk of canine mammary gland tumour (CMT) development. This study aimed to determine the prevalence of CMT diagnosed at the Veterinary Histopathology Laboratory, Faculty of Veterinary Medicine, University Putra Malaysia, between 2006 and 2012 and to evaluate the proportion of breed types, neuter status and age on the odds of CMT development. Forty-eight cases with confirmed diagnosis of CMT on histopathology were reviewed retrospectively. Thirty-nine (81.25%) were diagnosed as adenocarcinoma and 8.33% (n=4) for each squamous cell carcinoma and mixed cell tumour respectively. Adenoma was only diagnosed in one CMT. The prevalence of CMT in this study is 39%. When CMT cases were compared with all other diagnosis in dogs, CMT was significantly more in adult dogs (p=0.032, logistic regression 0.012) and intact dogs (p=0.009, logistic regression, (0.003). When CMT cases were compared with other types of neoplasia, significant association with CMT was observed in pure breeds (p=0.025) and intact dogs (p=0.000034, logistic regression 0.00042). This study found that pure breed dogs, intact dogs and older dogs (>5years) have higher odds of having CMT.